Randomized controlled trial of a web-based multi-modal therapy program for executive functioning in children and adolescents with unilateral cerebral palsy - M Piovesana, A.; Ross, S.; Lloyd, O.; Whittingham, K.; Ziviani, J.; Ware, R.; Boyd, Roslyn (Informa Healthcare, 2016)
Purpose state: Determine the efficacy of Move-it-to-improve-it (Mitii™), a multi-modal web-based program, in improving Executive Function (EF) in children with unilateral cerebral palsy (UCP). Method: Participants (n = 102) were matched in pairs then randomized to: intervention (Mitii™ for 20 weeks; n  = 51; 26 males; mean age = 11 years 8 months (SD = 2 years 4 months); Full Scale IQ = 84.65 (SD = 15.19); 28 left UCP; GMFCS-E&R (I = 20, II = 31) or waitlist control (n = 50; 25 males; mean age = 11 years 10 months (SD = 2 years 5 months); Full Scale IQ = 80.75 (SD = 19.81); 20 left UCP; GMFCS-E&R (I = 25, II = 25). Mitii™ targeted working memory (WM), visual processing (VP), upper limb co-ordination and physical activity. EF capacity was assessed: attentional control (DSB; WISC-IV); cognitive flexibility (inhibition and number-letter sequencing DKEFS); goal setting (D-KEFs Tower Test); and information processing (WISC-IV Symbol Search and Coding). EF performance was assessed via parent report (BRIEF). Groups were compared at 20 weeks using linear regression (SPSS 21). Results: There were no significant between group differences in attentional control (DSB; p = 0.20;CI= −0.40,1.87); cognitive flexibility (Inhibition, p = 0.34; CI= −0.73,2.11; number/letter sequencing, p = 0.17; CI= −0.55,2.94); problem solving (Tower; p = 0.28; CI= −0.61,2.09), information processing (Symbol; p = 0.08; CI= −0.16, 2.75; Coding; p = 0.07; CI= −0.12,2.52) or EF performance (p = 0.13; CI= −10.04,1.38). Conclusion: In a large RCT, MitiiTM did not lead to significant improvements on measures of EF or parent ratings of EF performance in children with UCP.Implications for rehabilitation - A large RCT of the multi-modal web based training; Move It to Improve It (MitiiTM) improves motor processing, visual perception, and physical capacity but does demonstrate statistically significant improvements or clinical significance in executive function in children with mild to moderate unilateral cerebral palsy (UCP). -MitiiTM training completed by an intervention group was highly variable with few children reaching the target dosage of 60 h. Technical issues including server and internet connectively problems lead to disengagement with the program. - Web-based training delivered in the home has the potential to increase therapy dose and accessibility, however, MitiiTM needs to be tailored to include tasks involving goal-setting, more complex problem solving using multi-dimensional strategies, mental flexibility, switching between two cognitively demanding tasks, and greater novelty in order to increase the cognitive component and challenge required to drive changes in EF.